Patterns and trends in continuous glucose monitoring utilization among commercially insured individuals with type 1 diabetes: 2010-2013 to 2016-2019 - Lacy, Mary E.; Lee, Katherine E.; Ataç, Ömer; Heier, Kory; Fowlkes, John; Kucharska Newton, Anna; Moga, Daniela C. (My University, 2024)
Prior studies suggest that only ?30% of patients with type 1 diabetes use continuous glucose monitoring (CGM), but most studies to date focused on children and young adults seen by endocrinologists or in academic centers. This study examined national trends in CGM utilization among commercially insured children and adults with type 1 diabetes. Overall, CGM utilization was 20.12% in 2010-2013 and 49.78% in 2016-2019, reflecting a 2.5-fold increase in utilization within a period of <10 years. Identifying populations with low CGM use is a necessary first step in developing targeted interventions to increase CGM uptake.
Keywords: Type 1 Diabetes; Continuous Glucose Monitoring (CGM)